2006
DOI: 10.1074/jbc.m512556200
|View full text |Cite
|
Sign up to set email alerts
|

The GTP-binding Protein YlqF Participates in the Late Step of 50 S Ribosomal Subunit Assembly in Bacillus subtilis

Abstract: Bacillus subtilis YlqF belongs to the Era/Obg subfamily of small GTP-binding proteins and is essential for bacterial growth. Here we report that YlqF participates in the late step of 50 S ribosomal subunit assembly. YlqF was co-fractionated with the 50 S subunit, depending on the presence of noncleavable GTP analog. Moreover, the GTPase activity of YlqF was stimulated specifically by the 50 S subunit in vitro. Dimethyl sulfate footprinting analysis disclosed that YlqF binds to a unique position in 23 S rRNA. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 50 publications
9
111
1
Order By: Relevance
“…Indeed, depletion of these proteins in bacterial cells leads to a decrease in 70S ribosomes with a buildup of 50S and 30S subunits (36,43,46). In contrast, both RbgA and HflX have been shown to bind to the 50S subunit and are required for its biogenesis, as cells depleted for RbgA show a reduction in 70S ribosomes, whereas free 50S subunits are completely missing (40,42,(47)(48)(49). HflX has also been implicated as a ribosome-splitting factor, involved in rescuing stalled ribosomes during stress (50).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, depletion of these proteins in bacterial cells leads to a decrease in 70S ribosomes with a buildup of 50S and 30S subunits (36,43,46). In contrast, both RbgA and HflX have been shown to bind to the 50S subunit and are required for its biogenesis, as cells depleted for RbgA show a reduction in 70S ribosomes, whereas free 50S subunits are completely missing (40,42,(47)(48)(49). HflX has also been implicated as a ribosome-splitting factor, involved in rescuing stalled ribosomes during stress (50).…”
Section: Resultsmentioning
confidence: 99%
“…Although the basic mechanisms of late assembly of the 50S subunit differ between E. coli and B. subtilis, the 45S particles share some common properties. As in the E. coli 45S precursor, substoichiometric levels of L16, L27, and L36 are present in the 45S particle that accumulates in the B. subtilis rbgA mutant (36,37,41). In addition, cryo-EM structures revealed that H38 and 5S rRNA are not yet oriented and that domains IV and V are not properly built up, in the B. subtilis 45S particle (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…RbgA/YlqF is an essential GTPase required for the proliferation of B. subtilis (36,37). Depletion of RbgA or expression of a dominant-negative mutant of RbgA resulted in accumulation of the 45S particles (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been experimentally demonstrated that B. subtilis ylqF encodes a GTP-binding protein that participates in the late step of 50S ribosomal subunit assembly (Matsuo et al, 2006). Moreover, ylqF has been shown to be an essential gene in B. subtilis (Uicker et al, 2007).…”
Section: Results Lmo1273 Encodes An Rnase H Homologuementioning
confidence: 99%
“…The two distal genes of the locus (lmo1272 and lmo1273), which are co-transcribed with the SPase I genes (Raynaud & Charbit, 2005), encode proteins sharing significant similarities with the YlqF and RnhB proteins, respectively, of Bacillus subtilis. In the latter organism, RnhB is involved in RNA-DNA heteroduplex degradation (Itaya et al, 1999;Ohtani et al, 1999a) and YlqF participates in ribosome biogenesis (Matsuo et al, 2006;Uicker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%